The students’ error analysis in writing descriptive texts - Gazul Fiqri Zaman; Ikariya Sugesti; Dila Charisma (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2020)
This study aimed to find out and analyze students’ error analysis at three student’s categories in writing descriptive text on paragraph-based writing subject. The analysis involved students’ writing ability in developing the ideas, organizing the ideas, vocabulary, grammar, punctuation, and the elements of descriptive text include generic structure and language features. The design of this study was case study under qualitative approach. There were 9 students from three categories as the subject of this study. The categories were high, medium, and low-level students at the fourth-semester of English Education Department at one of private university in Cirebon, West Java in the academic years of 2019/2020. The data were taken from student’s descriptive writing text and interview. The findings showed that the most errors from three students’ categories were grammatical errors, and how they arrange the elements of descriptive text. The total numbers of errors committed by students were 50 items, which include grammatical error with 40 items and the percentage 80%, generic structure error with 3 items and the percentage 6%, language features error with 7 items and percentage 14%. The most error made by the students are grammatical error with 40 items and the percentage 80%. It can be concluded that the students made grammatical errors, it is because they lack of vocabulary mastery and lack of grammar rules. Keywords: students’ error analysis; writing; descriptive text